Liturgy and Biblical interpretation : the Sanctus and the Qedushah - Selvén, Sebastian (Reading the Scriptures., 2021)
"What happens to the Bible when it is used in worship? What does music, choreography, the stringing together of texts, and the architectural setting itself do to our sense of what the Bible means--and how does that influence our reading of it outside of worship? In Liturgy and Biblical Interpretation, Sebastian Selvén answers questions concerning how the Hebrew Bible is used in Jewish and Christian liturgical traditions and the impact this then has on biblical studies. This work addresses the neglect of litrugy and ritual in reception studies and makes the case that liturgy is one of the major influential forms of biblical reception. The case text is Isaiah 6:3 and its journey through the history of worship." -- From back cover.